Trends in construction and demolition waste management: current approaches and emerging strategies - Sobral, Joyce Ingrid de Arandas; Lafayette, Kalinny Patrícia Vaz; Bezerra, Jonas da Silva; Paz, Diogo Henrique Fernandes da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – This study aims to analyze the results of research investigating he use of Construction and Demolition Waste (CDW) as a subsidy for soil improvement in landslide-prone areas, through a Systematic Literature Review (SLR). Methodology – It is applied research, conducted through an SLR without temporal restriction, using the following search terms: construction and demolition waste, construction waste, soil improvement, and landslides. The methodological phases involved database search and selection, data extraction, and both descriptive and bibliometric analyses. Originality/Relevance – The research addresses the theoretical gap related to the systematization of scientific evidence on the geotechnical potential of CDW, highlighting the lack of consolidated studies regarding its application in landslide-prone areas, while emphasizing its importance for urban sustainability. Results – The study reveals research trends, publication frequency, and methodological approaches, confirming the potential of CDW as an alternative material for soil property improvement. Theoretical/Methodological Contributions – This study strengthens the understanding of the use of construction waste as a geotechnical solution, while pointing out directions for future research based on more robust experimental analysis and field application. Social and Environmental Contributions – The findings reinforce that the use of CDW is an economically viable and environmentally sustainable alternative, promoting proper waste management, reducing pressure on natural resources, and contributing to the mitigation of landslide risks in vulnerable urban areas.